Retest Reliability of Integrated Speed–Accuracy Measures. (June 2022) - Bakun Emesh, Tamar; Garbi, Dror; Kaplan, Alon; Zelicha, Hila; Yaskolka Meir, Anat; Tsaban, Gal; Rinott, Ehud; Meiran, Nachshon
Cognitive tasks borrowed from experimental psychology are often used to assess individual differences. A cardinal issue of this transition from experimental to correlational designs is reduced retest reliability of some well-established cognitive effects as well as speed–accuracy trade-off. The present study aimed to address these issues by examining the retest reliability of various methods for speed–accuracy integration and by comparing between two types of task modeling: difference scores and residual scores. Results from three studies on executive functions show that (a) integrated speed–accuracy scoring is generally more reliable as compared with nonintegrated methods: mean response time and accuracy; and (b) task modeling, especially residual scores, reduced reliability. We thus recommend integrating speed and accuracy, at least for measuring executive functions.